Патологія репродуктивних органів у жінок із метаболічним синдромом - Дем'яненко, Л. В.; Яроцький, М. Є. (Clinical Endocrinology and Endocrine Surgery, 2011)
In the review possible variants of female reproductive system pathology appearing against the background of metabolic homeostasis changes are described in detail. The influence of metabolic syndrome presence on pathogenesis and clinical progression of the uterus and ovaries diseases in case of combined pathology in women is shown.